Are people with severe mental illness ready for online interventions? Access and use of the Internet in Australian mental health service users. (June 2017) - Thomas, Neil; Foley, Fiona; Lindblom, Katrina; Lee, Stuart
Objectives: The Internet is increasingly used in mental health service delivery, but there are significant potential barriers to Internet access for persons with severe mental illness (SMI). There is a need to understand this group's access to, and confidence with using, the Internet, and current views on using online resources as part of mental healthcare. Method: A survey was conducted of 100 consumers attending a specialist mental health service in Melbourne, Australia. Results: Approximately three-quarters of participants had regular access to the Internet, and two-thirds used the Internet weekly or more. Half of the sample used email at least weekly, and a third were regular users of social networking sites. Internet access was often via mobile devices. Only a minority of participants used the Internet for mental health information, with video streaming and general websites accessed more often than peer forums for mental health content. Most participants were positive about their mental health worker using tablet computers with them in appointments for delivery of mental health materials. Conclusion: Most people with SMI are active Internet users and, therefore, able to use interventions online.